Pengaruh Metode Drill Terhadap Kemampuan Servis Pendek Permainan Bulu Tangkis Putra Ekstrakurikuler Smp Negeri 19 Palembang - M. Ricky Athallah; M. Taheri Akhbar; Daryono (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2023)
This research aims to determine the effect of the drill method on short serve ability in extracurricular men's badminton games Public Middle School 19 Palembang. The population in this study was male students extracurricular activities at SMP Negeri 19 Palembang numbered 14 people, while the sample. This research uses the Census or Total Sampling technique. Census Techniques or Total Sampling is a sampling technique where all. All members of the population are sampled. Method in this research Using experiments, this research also includes one group design techniques pre-test and post-test design with treatment 16 times with instruments in the form of short service test. The research results obtained show that ????ℎ???????????????????? greater than ???????????????????????? (5,000 > 2.40), thus it can be interpreted from Overall, using drill training has an influence which is significant in drill method training on short feather service ability Men's extracurricular badminton at SMP Negeri 19 Palembang